Problem Based Learning Berbantuan Loose Parts Terhadap Kompetensi Pedagogik Guru PAUD - Wahyutami, Kriswanti; Madyawati, Lilis; Sulistyaningtyas, Reza Edwin (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2023)
ABSTRACT This study aims to determine the presence or absence of the effect of Problem Based Learning assisted by Loose Parts on the pedagogical competence of early childhood education teachers in Salaman District and Borobudur District. This study uses a design with the type of one group Pretest-Posttest by making initial measurements and final measurements. The subjects of this study were early childhood teachers from Salaman District and Borobudur district with a total of 30 subjects, each district represented by 15 teachers. In this study, researchers used purposive sampling technique. The research method used is the questionnaire method (questionnaire) and interview method, the preparation of which is based on aspects and indicators of pedagogical competence and then developed into items of questions that will be distributed to the subject. Data analysis technique used is non parametric statistical test with SPSS 25.0 for windows computer program with Wilcoxon Signed Ranks Test. The results of this study indicate that problem based learning assisted by loose parts has no effect on the pedagogical competence of early childhood teachers as evidenced by the results of the Wilcoxon signed ranks test Z count of -1,852 with Asymmp.Sig (2-tailed) is 0.064 with an average comparison of the initial measurement score of 87.33 and the final measurement of 94.20 after treatment in the form of providing training using problem based learning assisted by loose parts. The results of the study can be said that the activities using problem based learning assisted by loose parts there is no significant effect on the pedagogical competence of early childhood teachers. Key Words: Problem Based Learning, Loose Parts, pedagogic competence, early childhood teacher